2016
DOI: 10.1007/s10853-016-0333-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solution treatment on spinodal decomposition during aging of an Fe-46.5 at.% Cr alloy

Abstract: Spinodal decomposition is a key phase transition in advanced materials and a significant effort is paid to the quantitative modeling of the phenomenon. The initial materials condition is often assumed to be random during modeling, but this may be an oversimplification. In this work, the effect of solution treatment above the miscibility gap, on spinodal decomposition during subsequent aging, has been investigated for an Fe-46.5 at.% Cr alloy. By atom probe tomography (APT), it is found that different extents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…Theoretical calculations predicted a similar tendency for the short-range order (SRO) parameter with a change of sign with increasing Cr content [17][18][19][20][21]. The tendency of Cr clustering in Fe-Cr alloys with higher Cr contents has also been shown by Zhou et al [10,11,22].…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Theoretical calculations predicted a similar tendency for the short-range order (SRO) parameter with a change of sign with increasing Cr content [17][18][19][20][21]. The tendency of Cr clustering in Fe-Cr alloys with higher Cr contents has also been shown by Zhou et al [10,11,22].…”
Section: Introductionsupporting
confidence: 60%
“…5f. However, it has been found that, at present, this effect seems to be difficult to handle even with atomistic simulations [11]. Further work on the modeling of the effect of the initial structure on the PS kinetics is therefore necessary to find a viable modeling route.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the potential candidates for cladding and structural materials in future fusion reactors, Fe–Cr alloys, the basic alloy of high-chromium duplex stainless steels, exhibit a combination of beneficial properties [1,2,3,4]. The separation of the two-phase mixture of Fe-rich α phase and nanoscale Cr-rich α′ phases in ferrite [1,3] can induce embrittlement by enhancing the hardness of the alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the phase separation in Fe–Cr alloys has attracted a great deal of attention [5,6,7,8,9,10,11]. The clustering of Cr atoms inside the miscibility gap of Fe–Cr alloys was studied by Zhou et al [1] by kinetic Monte Carlo simulations and atom probe tomography (APT) experiment. Dahlström et al [8] studied the initial stage phase separation in Fe–Cr alloys by 3D-APT, and their results showed that phase separation is related to the nanostructure evolution and that Cr-rich regions form at the initial stages of decomposition.…”
Section: Introductionmentioning
confidence: 99%